Factors Associated with Compliance With Antenatal Care Visits Among Pregnant Women at Kadungora Public Health Center: A Cross-Sectional Study - Elang Mohamad Atoilah; Mohamad Ridwan Rifai; Arum Siwiendrayanti; Siti Hernina Bintari (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Compliance with antenatal care (ANC) visits is essential for monitoring pregnancy, detecting complications early, and reducing maternal and neonatal risks. However, regular ANC utilization remains challenging at the primary health care level, including at Kadungora Public Health Center. Objective: This study aimed to identify factors associated with ANC visit compliance among pregnant women, particularly maternal knowledge, attitudes, and husband support. Methods: A quantitative correlational study with a cross-sectional design was conducted among 82 pregnant women in their first, second, or third trimester selected through purposive sampling. Primary data were collected using questionnaires and analyzed using univariate and bivariate analyses. Results: Most pregnant women were noncompliant with ANC visits (59.8%), had low knowledge (65.9%), negative attitudes (70.7%), and inadequate husband support (53.7%). Knowledge (p < 0.001; OR = 6.03; 95% CI: 2.22–16.39), attitude (p = 0.002; OR = 4.82; 95% CI: 1.74–13.37), and husband support (p = 0.002; OR = 4.13; 95% CI: 1.61–10.54) were significantly associated with ANC visit compliance. These findings indicate that ANC compliance is influenced by both individual and family-related factors. Conclusion: Strengthening ANC education, promoting positive maternal attitudes, and actively involving husbands in maternal health programs are important strategies for improving ANC visit compliance at Kadungora Public Health Center.